Multicultural Character Formation in Islamic Religious Education - Mohamad Alifian Zanuar; Thoriq Al-Anshori; Dwi Mariyono (Newinera Publisher, 2026)
The implementation of multicultural education in Indonesia often encounters epistemological challenges, namely the dominance of Western educational theories that tend to be secular and only focus on socio-cognitive engineering, while ignoring the spiritual dimension that is the core of Islamic Religious Education. This condition triggers disparities in students who may understand tolerance intellectually, but are emotionally and spiritually fragile. This article seeks to reconstruct the position of Islamic Religious Education as the main discursive authority in character education, by making local wisdom in the Book of Jawahirul Adab as a pedagogical case study to fill this spiritual void. Using a qualitative approach with content analysis methods and contextual hermeneutics, this study dialogues the dimensions of James A. Banks' multicultural education with the concept of tazkiyatun nafs (purification of the soul). The results of the comparative analysis show that Islamic ethics provides axiological reinforcement to Banks' theory through the